In vitro Antibacterial Activity and Wound Healing Effects of Achillea millefolium Essential Oil in Rat - Mohammad Reza Ghasemi; Akram Ranjbar; Pari Tamri; Shabnam Pourmoslemi; Alireza Nourian; Dara Dastan (Korean Pharmacopuncture Institute, 2023)
Objectives: In this study we aimed to evaluate the in vitro antibacterial activity and wound healing properties of Achillea millefolium essential oil (AMEO) in full-thickness wound model in rat. The antibacterial activity of AMEO was evaluated against Staphylococcus aureus and Pseudomonas aeruginosa using the broth dilution method.Methods: The 2 cm × 2 cm full-thickness excisional wounds were created on the back of animals. Topical therapy was applied twice a day using 1%, 2%, and 3% w/w AMEO ointments, and the measurement of the wounds area was carried out every 3 days, after that the wound closure percentage was calculated in these days. Hydroxyproline content and histopathological evaluation of wound tissue samples were carried out on day 7 and 14 post wounding. Eucerin was used for the treatment of vehicle control group and negative control group received no treatment. Results: Our results revealed the bacteriostatic activity of AMEO against S. aureus and P. aeruginosa. Wound healing activity evaluation of AMEO showed the significant increase (p < 0.05) in the wound closure percentages in rats treated with AMEO 1% and 2% comparing to those of non-treatment group. In addition, hydroxyproline contents of tissue significantly (p < 0.01) increased in AMEO 1% and 2% comparing to non-treatment group. Histopathological evaluations of wound tissue samples on day 7 and 14 demonstrated higher accumulation of collagen fibers, reduction of edema and inflammation and also formation of tissue appendages in 1% and 2% AMEO treated groups in comparison with non-treatment group.Conclusion: The results of this study indicated that AMEO has the potential to be used as a safe and effective wound healing agent.